ROV cruises of the pockmarks Chez-le-Bart (CB), Treytel (TR), and La Lance (LL) in Lake Neuchatel, Switzerland in 2017 - Stefanie B Wirth; Damien Bouffard; Jakob Zopfi (PANGAEA, 2020)
A Remotely Operated Vehicle (RB600, Eprons Latvia) was used to survey the giant pockmarks. The ROV was equipped with a 360° sonar (SeaPrince, Tritech) and registered video material in VHS and HD quality. A light CTD probe (DCX-22-CTD, Keller Switzerland) was mounted on the ROV that continuously logged (2s interval) the temperature and the electrical conductivity of the water, as well as the pressure that was later transformed into water depth.